Reconfigurable Multi-Beam Dual-Band Antenna based on Vee Dipoles - Snehalatha, L.; Pathak, N. P.; Manhas, S. K. (Advanced Electromagnetics, 2018)
This paper presents a novel antenna configuration to support reconfigurable multi-beam feature with dual-band capability. The proposed design uses four double Vee dipoles with their arms printed on either sides of a substrate and fed through a single coaxial input probe. A single directional beam that can be configured in four directions at quadrature angle in the azimuth (xy-plane) and corresponding dual, triple and quad beams have been obtained by controlling the state of four PIN diodes. A prototype of the proposed antenna has been designed and fabricated. Measured antenna parameters are in good agreement with that of simulated parameters. This highly planar antenna shows similar radiation patterns at both design frequencies enabling concurrent dual-band communication for all fifteen possible beam configurations.